Saga (2012), volume 5 ebook - Vaughan, Brian K. (Saga (2012), 2015)
While Gwendolyn and Lying Cat risk everything to find a cure for The Will, Marko makes an uneasy alliance with Prince Robot IV to find their missing children, who are trapped on a strange world with terrifying new enemies. Collects SAGA #25-30.. Author: Brian K. Vaughan. Illustrator: Fiona Staples . 2015 Brian K. Vaughan & Fiona Staples.